f ( 1 + x 2 ) = x 2 ( 1 + 2 0 1 7 ) x 2 + 2 2 x + 2 , x = 0
Let function f be defined as above. Find the value of f ( 2 0 1 8 − 2 0 1 7 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For completeness, we should ensure that there is a corresponding value of x which gives us 1 + x 2 = 2 0 1 8 − 2 0 1 7 .
For example, we cannot determine what f ( 1 ) would be equal to.
f(1)=sqrt(2017)+1
Log in to reply
What value of x allows you to draw that conclusion?
Are you assuming that the function is continuous?
Problem Loading...
Note Loading...
Set Loading...
f ( 1 + x 2 ) ⟹ f ( 2 0 1 8 − 2 0 1 7 ) = x 2 ( 1 + 2 0 1 7 ) x 2 + 2 2 x + 2 = 1 + 2 0 1 7 + x 2 2 + x 2 2 = 2 0 1 7 + ( 1 + x 2 ) 2 = 2 0 1 7 + ( 2 0 1 8 − 2 0 1 7 ) 2 = 2 0 1 8
Note that when 1 + x 2 = 2 0 1 8 − 2 0 1 7 ⟹ x ≈ 0 . 0 3 2 5 7 0 9 5 7 , substituting it in the equation we get 2018 as answer.